A Google Classroom-Based Learning Management System: Empirical Evidence from SEEU (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2017)
The use of e-learning in a higher education institution is identified by the implementation of Learning Management Systems (LMS). South East European University’s LMS experience is longer than a decade. From last year SEE – University is adopting Google Classroom (GC). However, despite adoption of these systems, there are considerable challenges facing the usage of the systems. Hence, a tool has been developed to track the activity of the teachers in the system and to analyze the factors that maximize its usage. Moreover, a module for course and users’ management was also implemented. The purpose of this paper is to introduce a new approach of investigating the usage of GC, i.e. identifying the determinants of undertaking GC activities, by conducting empirical analysis for the case of SEEU. Using SEEU Usage Google Classroom Report & Analysis Data for 2016–2017 (SUGCR dataset 2017), we argue that (i) GC activities are affected by demographic characteristics and (ii) level, number of courses, and department affect the usage of GC. We apply appropriate estimation technique such as mlogit methodology. Identifying factors which encourage GC activities, with special emphasis on SEEU, might be of crucial importance for Higher Education academic leaders as well as software developers who design tools related to fostering GC.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.